Assessments of community pharmacists perceptions of the pros and cons of the home delivery of medications service in Sanaa, Yemen - Halboup, Abdulsalam M.; Alzoubi, Karem H.; Harun, Sabariah Noor; Alnono, Badr; Al-Khazzan, Abdulrazzaq; Zawiah, Mohammed; Al-Ashwal, Fahmi Y.; Sallom, Hebah; Abu-Farha, Rana (Taylor & Francis, 2025)
Home delivery of medications is an emerging service that can enhance treatment continuity, reduce travel burdens, and improve public health outcomes in low-resource settings like Yemen. However, community pharmacists perceptions in Sanaa remain unclear. To assess community pharmacists perceptions of home medication delivery services in terms of their advantages, disadvantages, and the factors influencing their acceptance. A cross-sectional survey was conducted among 375 community pharmacies in Sanaa from April to July 2023. Logistic regression identified factors affecting service acceptance. Of 390 pharmacies approached, 375 (96.2%) participated. The majority were male (85.9%), and 49.3% held a Bachelor of Pharmacy degree. More than two-thirds (68.3%) were aware of the service, 47.2% were willing to adopt it, and 31.7% currently offered it. The main disadvantages identified were dispensing errors (69.1%), verification limitations (71.5%), and challenges in marketing over-the-counter items (70.7%). In contrast, the primary advantages included facilitating treatment during pandemics (83.2%), aiding vulnerable populations (84.5%), providing convenience for parents (80.8%), and potentially reducing congestion in health facilities (72.0%). In multivariable analysis, willingness to adopt home delivery was higher among pharmacists currently providing it (AOR = 9.10), partially involved (AOR = 4.05), and those aware of it (AOR = 4.95; all p < 0.001). Most community pharmacists in Sanaa are aware of home medication delivery, and nearly half express a willingness to adopt it for its continuity of care, reduced facility congestion, and convenience. However, Concerns about medication errors remain, and acceptance is strongly influenced by awareness and involvement.